A Rare Case of Penile Lymphangioma Circumscriptum Treated with the Split-Thickness Skin Grafting Technique - Nurullah Hamidi (Journal of Urological Surgery, 2015)
Lymphangioma circumscriptum (LC) is an uncommon type of microcystic lymphatic malformation involving the skin and mucosa caused by saccular dilatation of lymphatic channels. Patients may suffer from edema, vesiculopustular lesions and lymphatic leakage. There are many treatment methods for the management of lymphangioma circumscriptum. In this paper, we present a 10-year-old patient who had penile edema treated with split-thickness skin grafting technique.